EXPERIMENTAL MODELING OF GEOSPHERE MOTIONS - SIVAK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Experimental investigation results gave a possibility of influence determination of dynamical processes that take face in the interior of the earth and on its surface on motion velocities of solid shells of the earth. It was established on the base of fulfilled harmonical analysis of earths crust buckling at its combinated loading on it surface and thin shell vibration forms, that they are similar.